"Survey on physical and Psychic complications of wife abuse on women " - Shahriary; T. Barough; N. Babaie; Gh. Amir Moradi; F (Tehran University of Medical Sciences, 2003)
Nowadays violence can be widely observed in many societies and one of these cases is domestic violence, the effect of which can be seen both on individuals and the society as a whole. If domestic violence persists it can result in divorce and in the long run may even result in murder, the effect of which both on the individual and the society is obvious. Disorder, homelessness and orphaned children are the disgraceful results of violence. This Research is a descriptive study on physical and Psychic complications of wife abuse on women who were referred to the Tehran legal medical authorities. The methods for gathering data were a questionnaire of personal information of both husband and wife, check list form consisting of 12 physical injuries and a standard test B K to measure the level of depression and self-esteem. The result of this research shows that the most prevalent physical and Psychic problem existent among women suffering from physical abuse from their husbands were as follows: physical injury and extreme fatigue (99%) severe depression (43%) and low self-esteem (65%).